Development of Leader-Member Exchange: A Longitudinal Test - Bauer, Talya N.; Green, Stephen G. (Academy of Management Journal, 1996)
This longitudinal study examines the development of leader-member-exchange (LMX) relationships via a model that extends and tests ideas presented but not yet fully tested in past theoretical models. New subordinates (n = 205) and their supervisors (n = 112) provided data that were used to test hypotheses stating that dyadic gender and personality similarity, member performance, and leader delegation would be incrementally and cumulatively related to LMX development. Support was found for relationships between the quality of leader-member exchange and positive affectivity similarity, performance, and delegation, but not for a relationship with gender similarity. In addition, it appears that good member performance may precede leader delegation.